2007
DOI: 10.1111/j.1743-6109.2007.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Intramuscular Testosterone Undecanoate for Treatment of Female-to-Male Transgender Individuals

Abstract: Aim Testosterone treatment is essential for the induction and maintenance of virilization of female-to-male transsexuals. This study tested the suitability of a novel testosterone preparation for this purpose. Methods Parenteral long-acting testosterone undecanoate (TU) was administered to 12 female-to-male transsexuals. Observations were made while subjects received treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 20 publications
7
48
0
Order By: Relevance
“…This study confirms the safety of TU treatment, and good levels of tolerance and compliance associated with the successful outcome of TU therapy [23,24]. Although a limited number of subjects were treated, and a control group was not included for ethical reasons, this model of gonadectomized subjects allows for the detection of the beneficial effects of exogenous T on muscle and bone in the absence of endogenously produced steroids.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This study confirms the safety of TU treatment, and good levels of tolerance and compliance associated with the successful outcome of TU therapy [23,24]. Although a limited number of subjects were treated, and a control group was not included for ethical reasons, this model of gonadectomized subjects allows for the detection of the beneficial effects of exogenous T on muscle and bone in the absence of endogenously produced steroids.…”
Section: Discussionsupporting
confidence: 71%
“…Using a previously devised protocol [21,25], two initial injections of TU were administered with a 6‐week interval, and subsequent doses were injected at 12‐week intervals. Secondary male characteristics were attained, and biochemical analysis showed significant decreases in plasma cholesterol and low‐density lipoprotein (LDL) [23], LH, prolactin (PRL), sex hormone binding globulin (SHBG), triglycerides, and increases in hemoglobin and hematocrit [24]. Adiponectin and leptin were significantly decreased in FtM subjects after 6 months of treatment with a different T ester, testosterone enanthate (TE) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Elbers et al demonstrated a decreased HDL and LDL particle size and increased TG concentration after testosterone administration in FTM transsexuals [8]. In contrast, Jacobeit et al [16] demonstrated that testosterone therapy in FTM transsexuals resulted in a statistically significant decrease in the level of TC and LDL, with no change in HDL. A recent meta-analysis of testosterone therapy in FTM transsexuals demonstrated an increase in TG and decrease in HDL in FTM transsexuals [3].…”
Section: Discussionmentioning
confidence: 99%
“…For induction and maintenance of virilization of FTM transsexuals, continuous androgen administration is necessary, both prior to sex reassignment surgery and thereafter for the remainder of the individual's lifetime to maintain virilization and, equally important, to prevent the sequelae of sex steroid deprivation (such as osteoporosis) following ovariectomy, which is part of sex reassignment surgery (2). Several reports document the use of parenteral TU in FTM (6)(7)(8). These reports indicate the feasibility and safety of the use of parenteral TU for the purpose of inducing virilization in FTM.…”
Section: Introductionmentioning
confidence: 99%